Anosmia Sebagai Faktor Prediktor Derajat Keparahan Ringan Pada Penderita COVID-19 Rawat Inap di Rumah Sakit Primasatya Husada Citra Surabaya - Hadi, Wiyono; Ernawati, Titiek; Novita, Bernadette; Wibowo, Tjipto; Supit, Vincentius Diamantino; Setiawan, Albert; Samsudin, Kevin; Erwin, Ferdinand (Majalah Kedokteran Indonesia, 2021)
Introduction: Anosmia is one of the clinical characteristics of COVID-19 patients. Anosmia was reported as the first symptom before other symptoms were discovered. Prior studies have shown anosmia implications as a favorable prognostic factor in COVID-19 patients. The research aim is to describe the characteristics of COVID-19 patients with anosmia and its correlation with disease severity.Methods: This study was a descriptive, cross-sectional, retrospective study with a total sample of 149 patients confirmed COVID-19. This research was conducted on hospitalized patients from March 1 to July 31, 2020, at the Primasatya Husada Citra Hospital Surabaya. Our study classified patients into two groups, with and without anosmia. The patient’s clinical characteristics were described in a table and odds ratio was calculated to determine the risk factors incidence of severe degree in COVID-19 patients.Results: The mean age of patients with anosmia was 32 years old, the patient’s gender was dominated with the female (63.2%). Patients with anosmia had lower severity, the odds ratio of having severe degree is 0.479. Patients with anosmia also had other symptoms such as cough, rhinorrhea, sore throat, tightness, headache, and muscle aches (p less than 0.05).Conclusion: COVID-19 patients with anosmia had lower severity than patients without anosmia.